PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA (PT PROVICES INDONESIA) - Edalsyah Mury Try Fajri; Ponco Priyantono (Jurnal Manajemen, 2020)
This research was conducted with the aim to find out and explain and explaining the influence between the variables of work discipline, compensation and performance. This research is a field study conducted at PT Provices Indonesia, a company engaged in the outsourcing sector, with a sample of 43 people using non-probability sampling through a purposive sampling approach. The analysis method uses descriptive statistical analysis, classical assumption test and t test. Based on the results of the t test the work discipline variable has t count 2.618> 2.020 t table with a significance of 0.012 <0.05, that work discipline has a positive and significant effect on employee performance. This shows that work discipline affects the performance of employees of PT Provices Indonesia. Then based on the results of the t test the compensation variable has a sig value. amounting to t count 3.053> t table 2.020 with a significance of 0.004 <0.05 that the compensation variable has a positive and significant effect on employee performance. This shows that compensation has an effect on the performance of PT Provices Indonesia employees. Based on the results of the R square test, the value is 0.395, this shows that the influence of work discipline and compensation variables on performance is 39.5% and the remaining 60.5% is influenced by other factors not examined. Keywords: work discipline, compensation and performance